2020
DOI: 10.29122/jbbi.v7i2.3944
|View full text |Cite
|
Sign up to set email alerts
|

OPTIMASI MEDIUM PERBANYAKAN IN VITRO TUNAS TALAS KALIURANG (Colocasia esculenta L.) DIPLOID DAN TETRAPLOID

Abstract: Optimation of In Vitro Shoot Proliferation Medium for Diploid and Tetraploid Kaliurang Taro (Colocasia esculenta L.) Taro cv. Kaliurang has a good taste and is tolerant to certain pests and diseases but its development is hampered by insufficient number of good quality plant materials. Quality improvement has been carried out through polyploidization. Shoot multiplication is an important step in micropropagation, which often needs specific formulation of culture medium. This study aimed to obtain an optimum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(12 reference statements)
1
1
0
Order By: Relevance
“…It indicated that the mutant plants had more shoots than the control plants. This is in line with Sinaga (2020), the difference in the characters of diploid and tetraploid taro Kaliurang is seen in the higher number of tetraploid shoots compared to the diploid. Furthermore, the different BAP concentrations also affected the number of shoots formed.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It indicated that the mutant plants had more shoots than the control plants. This is in line with Sinaga (2020), the difference in the characters of diploid and tetraploid taro Kaliurang is seen in the higher number of tetraploid shoots compared to the diploid. Furthermore, the different BAP concentrations also affected the number of shoots formed.…”
Section: Resultssupporting
confidence: 79%
“…In addition, the type of explant affects the number of roots formed. Sinaga (2020) reported that in taro Kaliurang, root growth in diploid clones was better than that of tetraploid clones. The DMRT test at α = 0.05 in Table 4 shows that the interaction of treatment media without BAP (z0) on control plants (mo) showed the best average root length of 2.41 cm which was significantly different from all mutant plant treatments (m1, m2, m3, m4).…”
Section: Resultsmentioning
confidence: 99%